2020
DOI: 10.1109/access.2020.2997378
|View full text |Cite
|
Sign up to set email alerts
|

A Chaos Disturbed Beetle Antennae Search Algorithm for a Multiobjective Distribution Network Reconfiguration Considering the Variation of Load and DG

Abstract: As the distributed generation (DG) in a power supply and the user load demand constantly change in an actual distribution network, multiobjective optimal network reconfiguration considering variations in load and DG has become a major concern, which is important and required to make system operations safe and economical. The aim is to minimize the sum of the active power loss, the sum of the load balancing index and the sum of the maximum node voltage deviation index simultaneously during the reconfiguration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In addition, the values of θ 1 and θ 2 obtained from Equations (15) and (16) are the same as those obtained using Equations (19) and 20:…”
Section: Theoretical Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the values of θ 1 and θ 2 obtained from Equations (15) and (16) are the same as those obtained using Equations (19) and 20:…”
Section: Theoretical Analysismentioning
confidence: 98%
“…In addition, the distribution network may be arbitrarily connected or separated to ensure optimum power supply to each line [15][16][17][18][19]. However, uncontrolled circulating current and inrush current are generated in the line when the voltage and phase between the lines are different from each other at the connection point (CP).…”
Section: Introductionmentioning
confidence: 99%
“…Users usually have relatively fixed demand proportion curves during a typical day in the same region and season, the loads can be described by demand proportion curves per day [36], which is shown in Fig.6. In general, the daily loads involve three categories: residential, industrial and commercial, the concrete parameters are given in Tables 2 and 3, they are shown in Fig.7.…”
Section: B Load Demandmentioning
confidence: 99%
“…where S∈{s|1,2,3} is the set of load types; s =1 is residential, s = is industrial, and s = 3 is commercial; PNi is the rated power of load node 'i'; and θsi represents the ratio of load type 's' in the total load of node 'i', δs represents the demand curves of load type 's' [36].…”
Section: B Load Demandmentioning
confidence: 99%
See 1 more Smart Citation